58.9k views
5 votes
Solve each exponential equation.
63^x = 36^x+1

User Sequenzia
by
6.1k points

2 Answers

3 votes

Answer:

x = 6.404

Explanation:

The given equation is:

63ˣ = 36⁽ˣ⁺¹⁾

Taking log on both side

x log(63) = (x + 1) log(36)

⇒ x log(63) = x log(36) + log(36)

⇒ x log(63) - x log(36) = log(36)

⇒ x {log(63) - log(36)} = log(36)


x = (\log(36))/(\log(63) - \log(36))


x = (1.556)/(1.799 - 1.556) {∵ log(36) = 1.556 and log(63) = 1.779}

x = 6.404

User MJay
by
5.9k points
4 votes

Answer:x=6.403

Explanation:

Given


63^x=36^(x+1)

taking natural log both side


\ln \left ( 63^x\right )=\ln \left ( 36\right )^(x+1)


x\ln \left ( 63\right )=\left ( x+1\right )\ln \left ( 36\right )


x\left ( \ln \left ( 63\right )-\ln \left ( 36\right )\right )=\ln \left ( 36\right )


x=(\ln \left ( 36\right ))/(\ln \left ( 63\right )-\ln \left ( 36\right ))


x=6.403

User Arjun Sreedharan
by
6.2k points